Clinical and electrophysiological findings of facial palsy in a case of hereditary gelsolin amyloidosis. Issue 2 (April 2023) - Yamakawa, Kaoru; Nishijima, Hironobu; Kubota, Akatsuki; Naruse, Hiroya; Baba, Shintaro; Fujimaki, Yoko; Kondo, Kenji; Toda, Tatsushi; Yamasoba, Tatsuya
Abstract: Hereditary gelsolin amyloidosis (HGA) is an autosomal dominant systemic amyloidosis, characterized by cranial and sensory peripheral neuropathy, corneal lattice dystrophy, and cutis laxa. We report a case of HGA presenting with bilateral facial palsy. A 70-year-old Japanese man presented with slowly progressive bilateral facial palsy and facial twitching, which had started in his 40s. His mother also had the same symptoms due to an unknown cause but rest of the family did not. He showed incomplete facial palsy with no frontal muscle movement and partial movement of the orbicularis oris and orbicularis oculi muscles. The patient showed no synkinesis. Electroneurography revealed symmetric low compound motor action potential amplitude of the orbicularis oris muscle, and a nerve excitability test showed a symmetric increase in the response threshold. Despite the partial voluntary movement of the orbicularis oculi muscle, bilateral blink reflexes were absent. He also showed facial spasms after contraction of the orbicularis oris muscle. Genetic testing revealed a heterozygous c.640G>A mutation (p. Asp214Asn); therefore, the patient was diagnosed with HGA. HGA related facial palsy showed moderate bilateral, upper blanch-dominant axonal degeneration of the facial nerve without reinnervation, and trigeminal nerve neuropathy.